2012
DOI: 10.1021/ja3004792
|View full text |Cite
|
Sign up to set email alerts
|

C(sp)–C(sp3) Bond Formation through Cu-Catalyzed Cross-Coupling of N-Tosylhydrazones and Trialkylsilylethynes

Abstract: Copper-catalyzed cross-coupling of N-tosylhydrazones with trialkylsilylethynes leads to the formation of C(sp)-C(sp(3)) bonds. Cu carbene migratory insertion is proposed to play the key role in this transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
100
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(108 citation statements)
references
References 36 publications
(25 reference statements)
3
100
0
2
Order By: Relevance
“…37 The sequence of migratory insertion/protonation from Cu(I) carbene, as outlined in eq 6, provides a new In the Cu-catalyzed reaction of N-tosylhydrazones and terminal alkynes, when trialkylsilylethyne is used as the substrate, the ethynylation product was isolated as the major product without detectable formation of allene products (Scheme 21). 38 This result demonstrates the potential of this type of cross-coupling reaction for the construction of C(sp)ÀC(sp 3 ) bonds, which has been a challenging problem in the past decade. 43 Further examination of the reaction scope has revealed that the reaction works with a wide range of N-tosylhydrazones derived from either aromatic and aliphatic aldehydes or ketones.…”
Section: Cross-coupling Reactions Catalyzed By Other Transition Metalsmentioning
confidence: 75%
“…37 The sequence of migratory insertion/protonation from Cu(I) carbene, as outlined in eq 6, provides a new In the Cu-catalyzed reaction of N-tosylhydrazones and terminal alkynes, when trialkylsilylethyne is used as the substrate, the ethynylation product was isolated as the major product without detectable formation of allene products (Scheme 21). 38 This result demonstrates the potential of this type of cross-coupling reaction for the construction of C(sp)ÀC(sp 3 ) bonds, which has been a challenging problem in the past decade. 43 Further examination of the reaction scope has revealed that the reaction works with a wide range of N-tosylhydrazones derived from either aromatic and aliphatic aldehydes or ketones.…”
Section: Cross-coupling Reactions Catalyzed By Other Transition Metalsmentioning
confidence: 75%
“…With the optimized reaction conditions to hand, the substrate scope of this reaction was explored by using various sub- Recently a viable alternative to the Sonogashira reaction at a saturated center, based on C(sp 3 )-C(sp) coupling, has been introduced by Wang et al [21] The synthetic approach to this through the incorporation of alkyl moieties by use of functionalized alkyl precursors has always been a challenge. The newly developed Cu I -catalyzed cross-coupling of N-tosylhydrazones 8 and trialkylsilylethynes 9 to yield ethynylated products 10 provided a new approach to solving the existing problem relating to the attachment of an alkyne moiety to the saturated center (Scheme 3) and since its development has become a commonly used method for the construction of C(sp)-C(sp 3 ) bonds.…”
Section: Carbon-carbon Bond Formationmentioning
confidence: 99%
“…1 The renewed interest in N-tosylhydrazones has occurred since the first palladium catalyzed cross-coupling of N-tosylhydrazones with aromatic bromides was documented by Barluenga group in 2007. 2 Leading scientists such as Barluenga and Valdés's group, Wang's group and others have contributed various transition metal catalyzed cross-coupling reactions of N-tosylhydrazones with alkynes, 3 azoles, 4 amines, 5 aryl boronic acids, 6 aryl sulfonates, 7 benzylic halides, 8 isocyanides, 9 trialkylsilylethynes, 10 and in the cascade carbonylations etc., 11 which have shown versatility and generality of this reagent to build useful functionalities for synthetic compounds. It is noteworthy that all of the above processes went through metal-carbenes intermediates which were generated in situ from N-tosylhydrazones while exposed to transition metals under basic and thermal conditions.…”
Section: Introductionmentioning
confidence: 99%